2006 International Conference on Simulation of Semiconductor Processes and Devices 2006
DOI: 10.1109/sispad.2006.282888
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of High Frequency Noise in SiGe HBTs

Abstract: A compact model solution, consistent with the system theory for correlated base and collector shot noise sources, was derived and implemented in the bipolar transistor compact model HICUM using Verilog-AMS. Simulations were performed using ADS 2005A. Results were tested against measured noise parameters for high-speed conventional and LEC doped SiGe HBTs. Perfect agreement between simulated and measured data confirmed model validity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Ramonas et al calculated noise parameters in SiGe HBTs using DD and HD simulations, and the results were verified against experimental values up to 25 GHz at current densities including high injection, without any additional parameter fitting [17]. Recently, Sakalas et al have used TCAD tools for noise model verification up to very high frequencies (beyond 100 GHz) where measurements are not available [18]. It was shown that noise simulated with the HD model yields good agreement with results from the Boltzmann transport equation solutions up to 500 GHz.…”
Section: Introductionmentioning
confidence: 96%
“…Ramonas et al calculated noise parameters in SiGe HBTs using DD and HD simulations, and the results were verified against experimental values up to 25 GHz at current densities including high injection, without any additional parameter fitting [17]. Recently, Sakalas et al have used TCAD tools for noise model verification up to very high frequencies (beyond 100 GHz) where measurements are not available [18]. It was shown that noise simulated with the HD model yields good agreement with results from the Boltzmann transport equation solutions up to 500 GHz.…”
Section: Introductionmentioning
confidence: 96%